2010
DOI: 10.1111/j.1944-9720.2010.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Study Abroad: Predicting Changes in Oral Skills

Abstract: Increasing numbers of students are opting for study abroad programs of 2 months or less while research on study abroad generally focuses on semester‐ or year‐long programs. This study quantitatively examines changes in students' spoken Spanish after 6 weeks in Argentina using native speaker ratings of student speech. The researcher then uses self‐report measures to determine which of the following variables predict improvements in speaking, pre‐program motivation and intercultural sensitivity, relationship wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 27 publications
8
80
1
Order By: Relevance
“…They found that during a summer stay of only 3-4 weeks student sojourners significantly improved their oral fluency and accuracy, in addition to listening comprehension. Martinsen (2010) discovered similar patterns for American leaners of Spanish in Argentina for a 6-weeks stay. The results demonstrate that after a short-term studying abroad most of the students have made small but significant progress in spoken Spanish.…”
Section: Linguistic Gains In Study Abroadsupporting
confidence: 52%
See 1 more Smart Citation
“…They found that during a summer stay of only 3-4 weeks student sojourners significantly improved their oral fluency and accuracy, in addition to listening comprehension. Martinsen (2010) discovered similar patterns for American leaners of Spanish in Argentina for a 6-weeks stay. The results demonstrate that after a short-term studying abroad most of the students have made small but significant progress in spoken Spanish.…”
Section: Linguistic Gains In Study Abroadsupporting
confidence: 52%
“…This section presents and reviews the empirical studies on the outcomes of language proficiency, particularly language skills, in study abroad context. The positive aspects of study abroad on students' oral proficiency have been generally supported by a large number of studies (Berg et al, 2009;Llanes & Muñoz, 2009;Martinsen, 2010). Berg et al (2009) examined the American study abroad students with control students learning the same language at home campus.…”
Section: Linguistic Gains In Study Abroadmentioning
confidence: 99%
“…In addition to these studies, there is a growing body of evidence linking cultural knowledge and skills to increased language learning during periods abroad (Alvord and Christensen, 2012;Bacon, 2002;Martinsen, 2010;Twombly, 1995;Vande Berg, Connor-Linton and Paige, 2009;Warden et al, 1995;Wilkinson, 1998a). The findings of these studies could be extremely valuable for the field of second language acquisition and teaching, since they indicate that greater cultural sensitivity actually leads to greater improvements in what might be termed linguistic or structural aspects of language learning, in addition to important social and attitudinal benefits.…”
Section: Language and Culture Learning In Study Abroadmentioning
confidence: 96%
“…Many studies have confirmed that students who go abroad tend to make more progress in improving their language skills than students who remain at home and attend classes on campus (e.g., Freed, Segalowitz, and Dewey, 2004;Brecht, Ginsberg and Davidson, 1993;Hernández, 2010). However, even among participants of study abroad there are some who do not demonstrate significant gains in their language skills Freed et al, 2004;Martinsen, 2010;Martinsen, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation